MENINGKATKAN HASIL BELAJAR IPS MELALUI MEDIA PEMBELAJARAN GAMBAR BERSERI PADA SISWA KELAS VIII SMP PEDULI BANGSA WOOI KECAMATAN OBI TIMUR KABUPATEN HALMAHERA SELATAN - Rehaji, Felix; Suaema, Andi; Halek, Dahri Hi (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
The purpose of this study is to determine the use of serial image learning media to improve the understanding of disaster mitigation in geography learning on natural disaster material for eighth grade students of SMP Peduli Bangsa Wooi, South Halmahera Regency. This study uses an action research type, which focuses on classroom activities so that the research is in the form of Classroom Action Research (CAR). This research was conducted at SMP Peduli Bangsa Wooi, South Halmahera Regency. The subjects of this study were 20 eighth grade students of SMP Peduli Bangsa Wooi. The techniques used in collecting the data include. Observation, Test, and Documentation. The use of Serial Image Media can improve the learning outcomes of eighth grade students in the Social Studies subject of natural disasters. This can be seen from the learning outcomes of students from cycle I and cycle II which have increased. Student learning completeness in cycle I was 61.35% and in cycle II was 86.45% with an increase of 21.1%.